Literature Study: Potential of Garcinia latissima Miq. for Skin Care - a Mini Review - Neneng Siti Silfi Ambarwati; Yesi Desmiaty; Mari Okatini Armandari; Sri Irta Widjajanti; Triastity, Sarinah; Yolanti (Journal of Natural Product for Degenerative Diseases, 2024)
The species Garcinia Latissima Miq. is native to Southeast Asia's tropical rain forests, primarily in Papua and Maluku. This plant is well-known for its thick-skinned fruit, used as a spice in traditional recipes. Garcinia Latissima Miq is also used in traditional medicine. Its use as a traditional medicine is because Garcinia Latissima Miq. has long been recognized as a source of phenolic compounds, and earlier research has shown that the chemicals extracted have biological activity as antioxidants, antibacterials, and antimicrobials. This study aimed to gather adequate information on the Garcinia Latissima Miq. plant's potential for usage as a cosmetic or skincare ingredient. A literature review was done in this study to obtain data from prior investigations. According to the findings of this investigation, the Garcinia Latissima Miq. plant possesses anti-elastase, which helps maintain skin elasticity, and contains flavonoids that inhibit tyrosinase in melanogenesis. Garcinia Latissima Miq. plant has the potential to maintain skin elasticity and brightness.